1997
DOI: 10.1152/ajpcell.1997.272.3.c886
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular acidosis activates c-Src

Abstract: The purpose of the present studies was to determine whether acidosis activates protein tyrosine kinase pathways. Incubation of MCT cells, a renal proximal tubule cell line, in acid media caused increased phosphotyrosine content of 60- to 70- and 120-kDa cytosolic proteins. Media acidification induced a twofold increase in c-Src activity that occurred within 30 s. Significant activation occurred with media pH changes as small as 0.07 pH unit accompanied by cell acidification of 0.06 pH unit. Sodium propionate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…A subsequent study identified the proto-oncogene c-Src as the cellular tyrosine kinase essential for this response (17). Activation of c-Src tyrosine kinase (herein referred to as c-Src) requires phosphorylation on an internal tyrosine residue, and changes in extracellular pH of 0.07 (equivalent to a change in bicarbonate concentration of 3-4 mM) were found to induce a detectable increase in phosphorylation of c-Src (18). Surprisingly, the phosphorylation of c-Src was greatest after only 90 seconds of cellular acidification, subsequently returning to a level slightly above baseline.…”
Section: Activation Of Nhe3 By Cytosolic Acidification Requires C-srcmentioning
confidence: 99%
“…A subsequent study identified the proto-oncogene c-Src as the cellular tyrosine kinase essential for this response (17). Activation of c-Src tyrosine kinase (herein referred to as c-Src) requires phosphorylation on an internal tyrosine residue, and changes in extracellular pH of 0.07 (equivalent to a change in bicarbonate concentration of 3-4 mM) were found to induce a detectable increase in phosphorylation of c-Src (18). Surprisingly, the phosphorylation of c-Src was greatest after only 90 seconds of cellular acidification, subsequently returning to a level slightly above baseline.…”
Section: Activation Of Nhe3 By Cytosolic Acidification Requires C-srcmentioning
confidence: 99%
“…The mice also showed defects in osteoclast formation and activity, with large osteoclasts small in number (28). TRPV4 shows a weak response to acid (29), and is activated by src under acidotic conditions (30), implying that TRPV4 could be activated during acidosis.…”
Section: Acid-sensing Machinerymentioning
confidence: 98%
“…Both Pyk2 and c-Src activation are required for acid to activate NHE3 activity. [59][60][61][62] Downstream from c-Src is endothelin-1 (ET-1) production and secretion by the proximal tubule. 53,63 The mechanism by which c-Src stimulates ET-1 secretion is not yet known.…”
Section: Adaptation To Metabolic Acidosismentioning
confidence: 99%
“…Both Pyk2 and c-Src activation are required for acid to activate NHE3 activity. [59][60][61][62] Downstream from c-Src is endothelin-1 (ET-1) production and ET-1/ETB mediates acid stimulation of NHE3 involving exocytic insertion of NHE3 into the apical membrane. This process requires an intact cytoskeleton, 65 and is associated with NHE3 phosphorylation.…”
mentioning
confidence: 99%